Differentiation of equine mesenchymal stem cells into cells of osteochondral lineage: potential for osteochondral tissue engineering. (1st November 2022) - Cheng, Hiu Wa; Chik, Tsz Kit; Weir, Joe; Chan, Barbara Pui
Abstract: Damage to the hyaline cartilage of the joint surface and osteochondral fractures are key factors leading to the development of osteoarthritis in racehorses, representing a significant cause of racehorse retirement. To tissue-engineer an osteochondral unit that is suitable for joint repair, incorporation of a zone of calcified cartilage should be considered so as to mimic its in vivo counterpart. To date, equine mesenchymal stem cells (eMSCs) have been reported to have multilineage differentiation potential. Yet the generation of a zone of calcified cartilage using eMSCs has not been reported. This work is an initial attempt to generate a zone of calcified cartilage using eMSCs as the single source of cells and collagen as the scaffolding material. Main advantages of using eMSCs over equine deep zone chondrocytes for the generation of a zone of calcified cartilage include no donor site morbidity and their ease of expansion in culture. Initially, we fabricated cartilage-like tissues and bone-like tissues in vitro by differentiating eMSCs toward chondrogenic and osteogenic lineages for 21 d, respectively. We then aggregated the cartilage-like and bone-like tissues together with a layer of undifferentiated eMSCs-collagen gel in between to generate a 3-layer osteochondral unit. A zone of calcified cartilage was found between the cartilage-like and bone-like layers after a 14-day culture in chondrogenic differentiation medium. These results provide a solution toward tissue engineering of equine osteochondral units with interfacial zone without using chondrocytes harvested from the deep zone of healthy articular cartilage, and contribute to the future development of osteochondral tissue engineering strategies for human cartilage injuries in the long run.